2008
DOI: 10.1007/s10344-008-0212-9
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to native bandicoots in an urban environment

Abstract: Urbanization along the eastern seaboard of Australia has increased the potential for conflict between humans and wildlife. The northern suburbs of Sydney are home to the southern brown (Isoodon obesulus) and the long-nosed bandicoot (Perameles nasuta). Both are known to enter yards of home owners causing a disturbance to yard plantings and an interaction with domestic pets. Understanding the driving factors behind the public's perception of bandicoots will enable wildlife managers to develop effective and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Gadd (2005) indicated that human-wildlife conflict may erode local support for conservation and it is clear that the public will tolerate some aspects of living with wildlife until these activities result in a safety concern or economic loss (Coluccy et al 2001;Dowle and Deane 2009). Our findings concur, as we found greatest levels of positivity among people who lived near the range while those who lived inside the range had the most accurate objective knowledge but moderate positive attitude.…”
Section: Regional Differencessupporting
confidence: 88%
See 1 more Smart Citation
“…Gadd (2005) indicated that human-wildlife conflict may erode local support for conservation and it is clear that the public will tolerate some aspects of living with wildlife until these activities result in a safety concern or economic loss (Coluccy et al 2001;Dowle and Deane 2009). Our findings concur, as we found greatest levels of positivity among people who lived near the range while those who lived inside the range had the most accurate objective knowledge but moderate positive attitude.…”
Section: Regional Differencessupporting
confidence: 88%
“…The attitudes of local communities towards wildlife may vary according to many factors such as gender (Hill 1998;Martino 2008), prior experience of wildlife (Dowle and Deane 2009), income (Gould et al 1989), region (Irby et al 1997), and education background (Williams et al 2002). Our results are consistent with the perspective that awareness of conservation values increases with levels of education (Ericsson and Heberlein 2003) as higher educated interviewees living inside the range of gazelle were more aware of its conservation.…”
Section: Factors Influencing Attitudesmentioning
confidence: 99%
“…The literature features regular analysis of place through the comparison of 'urban' and 'rural' populations (Bandara andTisdell 2003, Kendall et al 2006) and occupation through study of individuals with a livelihood or ownership link to the land/environment/wildlife and those without (referred to variously as 'lay' persons, 'enthusiasts' or the 'public', Responsive Management 2005, Stronen et al 2007). A growing body of literature also seeks to describe and understand the variation in attitudes towards wildlife management encountered with variation in the physical and social environment where wildlife are found and where its management occurs (Whittaker et al 2001, Siemer et al 2004, König 2008, Dowle and Deane 2009). This research particularly highlights the practical difficulties of managing wildlife in suburban and urban locations, along with the sometimes dramatic differences in attitudes held by the various social groups involved.…”
Section: Introductionmentioning
confidence: 98%
“…Questions were adapted from previous studies of wildlife attitudes in the context of humanwildlife conflict in other countries (Carlos et al, 2009;Dowle & Deane, 2009;Hill et al, 2007;Jonker et al, 2006;König, 2008). Responses were given on a 5-point scale where 1 = strong agreement and 5 = strong disagreement.…”
Section: Variables Measuredmentioning
confidence: 99%